Text Mining Sentiment Analysis on Mobile Banking Application Reviews using TF-IDF Method with Natural Language Processing Approach - Bimantara, Muhammad Dhuha; Zufria, Ilka (PT Mattawang Mediatama Solution, 2024)
As part of its efforts to improve digital banking services, PT Bank Rakyat Indonesia (Persero) Tbk (BRI) has launched a mobile banking application called BRImo. This move is in line with the global trend where financial institutions are increasingly focusing on digitalization to meet the evolving needs of customers who demand faster and more efficient accessibility to banking services. BRImo comes as an innovative solution to provide a better banking experience to BRI customers. This research was conducted to find out the reviews of the BRImo application on the App markets google playstore, In BRImo mobile banking's efforts to remain competitive with other mobile banking applications, understanding positive and negative reviews from users is very important. The fundamental issue that must be addressed is how to analyze positive reviews to strengthen the advantages of the BRImo app and identify negative reviews to address weaknesses that may hinder its competitiveness. This research was conducted to find out the reviews of the BRImo application on the App markets google playstore, In BRImo mobile banking's efforts to remain competitive with other mobile banking applications, understanding positive and negative reviews from users is very important. The method used in the calculation is TF-IDF and NLP approach and the calculation of SVM algorithm is trained using training data. The calculation results show that the model has an accuracy of 92%. or Precision Score of about 92%, Recall Score has 100% and F1 Score has 0.95 or approximately 95%.